Model Pengembangan Kepribadian di Pesantren - Muskinul Fuad (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
This study aims to describe the model of Muslim personality development that is developed based on in-depth observations of what is practiced by the pesantren community in order to develop the personality of their students. This research was conducted with a qualitative approach in the form of ethnography. Subjects were taken from three Islamic boarding schools in Purwokerto City, namely An-Najah Islamic Boarding School, Darussalam Islamic Boarding School, and ath-Thohiriyah Islamic Boarding School. The results showed that the Muslim personality development model practiced by the pesantren community was based on several principles and values ​​that were understood and practiced by the pesantren community, including scientific enthusiasm, independence, responsibility, simplicity, togetherness, leadership, and sincerity. The process of developing students' personality is done through understanding, exemplary, accustomed to, worshiping, and deepening the values ​​of pesantren. The Muslim personality development model that has been practiced in the pesantren community can be said as an answer to the need for a personality development approach that is appropriate to the religious cultural context of Indonesian society. This model is worth discussing as indigenous personality development, which is a pattern of personality development that is rooted in the values, perspectives, or traditions that exist in a community.